2021
DOI: 10.3390/agriculture11060498
|View full text |Cite
|
Sign up to set email alerts
|

Chia (Salvia hispanica L.) Seed Soaking, Germination, and Fatty Acid Behavior at Different Temperatures

Abstract: The temperature reduces the viability and seed vigor; however, the effect of temperature on imbibition and fatty acid profile has not been studied. Chia (Salvia hispanica L.) seeds have a substantial quantity of oil, making them a potential study model for fatty acid metabolism. Therefore, we explore the effect of temperature (10, 20, and 30 °C) on chia seed imbibition, germination, and fatty acid profile by GC-MS. Imbibition FI occurs within the first hour in all the treatments; while FII and FIIend elapse wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 85 publications
2
3
0
Order By: Relevance
“…Our observed optimal condition, i.e., the temperature(s) at which the germination percentage is high, and germination occurs the fastest, in this case, 25-35 • C, is almost ten degrees above the reported range [41]; this evidence agrees with our previous results [24] and with those observed by Paiva et al [25,26]. The differences in the germination of chia varieties generated by domestication are mainly associated with different capabilities to germinate and grow under different climatic conditions [27], like those varieties produced to grow during the long days of the northern hemisphere [45,46].…”
Section: Germinationsupporting
confidence: 93%
See 3 more Smart Citations
“…Our observed optimal condition, i.e., the temperature(s) at which the germination percentage is high, and germination occurs the fastest, in this case, 25-35 • C, is almost ten degrees above the reported range [41]; this evidence agrees with our previous results [24] and with those observed by Paiva et al [25,26]. The differences in the germination of chia varieties generated by domestication are mainly associated with different capabilities to germinate and grow under different climatic conditions [27], like those varieties produced to grow during the long days of the northern hemisphere [45,46].…”
Section: Germinationsupporting
confidence: 93%
“…Upon germination, the progressive depletion of oxygen generates conditions that almost achieve anaerobiosis, and fermentation is triggered as the main source of cellular ATP, supporting the reduction of electron transferring compounds, e.g., NAD and NADP, and inevitably leading to ROS (reactive oxygen species) accumulation [75]. In the case of S. hispanica, we observed that in a temperature range from 10 • C to 20 • C, germination undergoes a lag phase; above that temperature, germination increases exponentially as it approaches the optimal temperature, this evidence suggests that mucilage could have a temperature where its moisture-holding capacity changes, allowing germination to proceed more quickly; this agrees with our previous observations [24].…”
Section: Cardinal Temperature Determination By Linear and Non-linear ...supporting
confidence: 91%
See 2 more Smart Citations
“…For the analysis of the methyl esters of fatty acids, we followed the method of Cabrera‐Santos et al ( 2021 ). To identify the fatty acids, a gas chromatograph was used (GC; Agilent Technologies 6850), coupled with a mass spectrometer (MS; Agilent Technologies 5975C VL MSD).…”
Section: Methodsmentioning
confidence: 99%